Accurate Formula to Determine Resonant Frequency of Double Sided Printed Dipole Antenna. Issue 3 (4th May 2018) - Ghosh, R. P.; Patra, K.; Gupta, B.; Chowdhury, S. K.
ABSTRACT: Two arms of double-sided printed dipole antenna (DSPDA) are printed on opposite faces of a dielectric material. The antenna is fed by the printed version of two-wire parallel transmission line. This configuration has the advantages of high impedance bandwidth and low cross polarization. The width of each dipole arm is generally kept below 0.05λ0 to achieve high cross polar discrimination. However, it is observed that, in case of DSPDA the resonating length is different from that of the conventional half-wave dipole antenna. In this paper, we have proposed a semi-empirical but accurate formula to predict the resonant frequency for a given length of DSPDA. A prototype antenna is fabricated using the proposed formula which is validated against experimental results. Measured resonant frequency of the fabricated DSPDA matches closely with the theoretical one.